Meningkatkan Prestasi Belajar Siswa Melalui Strategi Giving Question and Getting Answer (GQGA) pada Materi Zakat Siswa Kelas VIII Mts Maslahiyah Krecek - Umam Ali Muchasan (LPPM IAI Hasanuddin Pare-Kediri, 2015)
The point of view in this research was the ways of teachers in upgrading student’s achievement in fikih through appropriate strategies in this era especially the question skill application as means to solve student’s problem at Mashlahiyah Islamic Junior High in Krecek. This research was intent on upgrading student’s achievement through Strategy Giving Question and Getting Answer (GQGA) application for eight students of Mashlahiyah Islamic Junior High in Krecek. Descriptive analysis was the researching method that was used in this research. The data was obtained by observation, distributing inquiries and test. This research was done by dual action cycle. The data analysis process consisted of data collection, respondent answering analysis, setting and fixing the data, setting before data, and concluding. Based on the research was done, it can be concluded that ability and the student’s achievement in Fikih about Zakat upgraded. It was shown with the less student that didn’t get perfect grade. It was pre-cycle (13 students), first cycle (7 students), and second cycle (0 student). It showed that the Giving Question an Getting answer (GQGA) application in studying process upgraded ability and the student’s achievement therefor hypothesis was acceptable.